Thermodynamics of the solid solution - Aqueous solution system (Ba, Sr, Ra)SO4 + H2O: I. The effect of strontium content on radium uptake by barite. (February 2018) - Vinograd, V.L.; Kulik, D.A.; Brandt, F.; Klinkenberg, M.; Weber, J.; Winkler, B.; Bosbach, D.
Abstract: Thermodynamic properties of mixing in the ternary (Ba, Sr, Ra)SO4 solid solution are determined using first principles based total energy calculations and Monte Carlo simulations. Two levels of theory, which correspond to the regular mixing and the generalized Ising model, are considered. The results show that the regular mixing parameters increase along the row of Ba-Ra, Ba-Sr and Sr-Ra binary systems proportionally to the squared difference of molar volumes of the end-members. The magnitudes of pairwise interactions similarly increase along the same row, manifesting a tendency to short-range ordering (SRO). In the (Ba, Sr)SO4 system the SRO effect is approximately equivalent to a 40% decrease in the value of the regular mixing parameter. The ternary solid solution is well described as a regular mixture with the binary parameters W BaRa = 2.47 ± 0.22, W BaSr = 4.95 ± 0.75 and W SrRa = 17.50 ± 1.40 kJ/mol. These values imply that admixing RaSO4 to the (Ba, Sr)SO4 solid solution stabilizes Ba-rich and destabilizes Sr-rich compositions. Consequently, an addition of a small amount of RaSO4 to a Sr-rich solid solution leads to a nucleation of a Ba- and Ra rich phase. This phenomenon, predicted in our thermodynamic modelling study, is directly confirmed by our experiments on recrystallizing a powder of celestite with traces of Ba in the presence of an aqueous Ra-bearing solution. At a measurably high content of Ra in the system Ra-uptake by celestite occurs via a formation of a Ra-rich phase. The aqueous concentration of Ra in such systems would be governed mainly by the common anion effect caused by the relatively high solubility of Sr-rich sulphates. At lower Ra contents the retention of Ra would be enhanced both by the common anion and the dilution effects. Our simulations with the GEM-Selektor code predict that the optimum condition for Ra uptake is achieved when the barite solid solution contains 10 ± 5 mol % of SrSO4 . Highlights: The mixing parameters of the (Ba, Sr, Ra)SO4 solid solution are determined from first principles. An addition of RaSO4 to a Sr-rich solid solution leads to a nucleation of a Ba- and Ra-rich phase. A small fraction of SrSO4 in the barite solid solution improves Ra-uptake.